Application of Artificial Intelligence Technology to Improve Responsiveness and Speed of Operations in Organizations - Bakar, Rochmad Abu; Hadiyati, Ayuni Asita (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2024)
This service aims to encourage the use of Artificial Intelligence (AI) technology in increasing the effectiveness of Advocates' work. The service process is carried out through literature studies and qualitative analysis that identify the role of AI in the four stages of Advocate case management. Of the four stages, not all can be assisted by AI because they are limited in handling complex human, intuitive, and ethical aspects. The implementation method includes collecting data from journals, books, and legal sources, processed to develop an effective AI application strategy for Advocates. The service is carried out in stages over several months. The results show that AI can accelerate legal analysis and support strategy in the planning stage, but still requires human involvement at other stages. The implication of using AI is increased efficiency, without replacing the important role of Advocates in aspects of legal complexity.